PROFITABILITAS DALAM MEMODERASI HUBUNGAN ANALISIS NON PERFORMING FINANCING TERHADAP PEMBIAYAAN MURABAHAH - Listiyowati, Listiyowati; Shalahudin, Muhammad Sahid (Universitas YPPI Rembang, 2023)
Murabahah financing in the sharia commercial banking sector is financing that is very popular with the public, because it has a lower level of risk. The aim of the research is to determine the effect of non-performing financing on murabahah financing with return on assets as a moderating variable. This research was conducted at Islamic commercial banks registered with the OJK in 2018-2022. By using a purposive sampling, sample of 50 banks was obtained. This experience method uses moderation regression analysis (MRA) test with a few data analysis method which is, normality test, heterokedastisitas test and autocorrelation test. The research results show that NPF has an influence on murabahah financing. This means that as long as sharia commercial banks are able to manage and regulate the risk management of the NPF value well, this will also be able to increase the level of murabahah financing. This is because sharia commercial banks will use other sources they have to reduce the existing high NPF value. and ROA is able to moderate the relationship between NPF and murabahah financing. This is because when the NPF increases and profits are able to provide good interactions, the bank does not experience a significant impact. When profits are able to provide a positive impact on NPF, then on the one hand murabahah financing experiences a decline. Because Islamic banks do not use profits to increase the level of murabahah financing, but profits are used to cover the NPF level owned by the company.